Performance research and Simulation analysis of magnetorheological torque servo device. Issue 4 (March 2021) - Sha, Shujing; Zhang, Fuhao
Abstract: This paper expounds the rheological mechanism of magnetorheological fluid and the working principle of magnetorheological moment servo, studies the relationship between excitation current and magnetic field strength, magnetic flux and magnetic flux potential, and analyzes and designs the magnetic circuit. The electromagnetic analysis of the magnetorheological moment servo device was carried out by ANSYS software, and the relevant information such as the distribution of magnetic field lines and magnetic induction intensity was analyzed. The relationship between excitation current and magnetic flux density was obtained by fitting the data under different excitation current. The quantitative relationship between the input current and output torque of the magne-orheological drive device is simulated by matlab software.